2021
DOI: 10.22541/au.162581754.46817995/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing soil organic carbon sequestration and yield stability simultaneously through combined no-tillage and straw return in wheat-maize rotation

Abstract: Knowledge about the changes in soil organic carbon (SOC) stocks and grain yields under different tillage and straw management is necessary to assess the feasibility and sustainability of conservation agriculture. An 8-year experiment was conducted in an intensive wheat (Triticum aestivum L.)–maize (Zea mays L.) rotation system in the southern Loess Plateau of China. Three tillage methods [control with no-tillage and straw removal (CK), no-tillage with straw stubbles 30–40 cm in height (NT), and rotary tillage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…In this study, we found that there were also complementary effects on nitrogen utilization resulting from the interplanting of cultivars with different nitrogen use efficiencies, which improved corn growth and grain yield. Previous studies confirmed that the interplanting of corn cultivars could optimize the canopy structure and increase the light use efficiency, leaf area index, and biomass, indicating that interplanting increased plant growth and the photosynthetic products allocated to roots [40,41]. Meanwhile, the root morphological characters of plants had the ability to self-regulate according to adjacent plants and attained an optimal distribution in the roots [42].…”
Section: Interplanting Promoted Plant Growth and Nitrogen Utilizationmentioning
confidence: 84%
“…In this study, we found that there were also complementary effects on nitrogen utilization resulting from the interplanting of cultivars with different nitrogen use efficiencies, which improved corn growth and grain yield. Previous studies confirmed that the interplanting of corn cultivars could optimize the canopy structure and increase the light use efficiency, leaf area index, and biomass, indicating that interplanting increased plant growth and the photosynthetic products allocated to roots [40,41]. Meanwhile, the root morphological characters of plants had the ability to self-regulate according to adjacent plants and attained an optimal distribution in the roots [42].…”
Section: Interplanting Promoted Plant Growth and Nitrogen Utilizationmentioning
confidence: 84%